2015
DOI: 10.4209/aaqr.2014.06.0108
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Source Apportionment of Submicron Particle Number Size Distributions in a Busy Street Canyon

Abstract: Street canyons are well-known hot spots due to the harmful exposure to high concentrations of atmospheric pollutants emitted mainly by motor vehicles. We report on measurements of air pollutants conducted in a street canyon in Stockholm (Sweden) in spring 2006. Particle number size distributions (PNSD) were measured in the 25-606 nm range, along with total particle number, light-absorbing carbon mass concentration (M LAC ), PM 10 , NO x , CO, traffic rate (TR), vehicle speed and meteorological variables. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 37 publications
2
10
0
2
Order By: Relevance
“…Diesel-powered vehicles, which are usually a smaller fraction of the fleet, make a proportionally large contribution to total number concentrations (Kittelson et al, 2006). For example, Krecl et al (2015) showed that 73% of BC particles in Stockholm come from diesel emissions, especially in the early hours at weekends.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel-powered vehicles, which are usually a smaller fraction of the fleet, make a proportionally large contribution to total number concentrations (Kittelson et al, 2006). For example, Krecl et al (2015) showed that 73% of BC particles in Stockholm come from diesel emissions, especially in the early hours at weekends.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the smaller-sized PM categories of PM 1.0 and ultrafine particulates in the < 100 nm range (UFP) have been attracting growing research attention (Young et al, 2013;Jayaratne et al, 2015;Krecl et al, 2015;Lin et al, 2015). The PM size is critical to its toxicity by inhalation.…”
Section: Introductionmentioning
confidence: 99%
“…Os particulados PTS e PI, com o CO e o NO 2 , apresentam picos pela manhã, entre 07h00 e 10h00, e no período das 17h00 às 22h00, horário de maior fluxo de veículos. Esses picos corroboram o observado por Gioda et al (2016), em estudo realizado no Rio de Janeiro, onde também foram verificados picos de poluentes nos horários de grande tráfego de veí-culos; também Krecl et al (2015), em estudo realizado em Estocolmo, identificaram picos de aumento de concentração de poluentes coincidindo com o aumento do número de veículos no trânsito. É possível verificar que a concentração de SO 2 sofre um acúmulo nas primeiras horas do dia até as 17h00 e posteriormente sofre redução até as 24h00, provavelmente devido à interação entre a radiação e o calor acumulado no final do dia.…”
Section: Resultsunclassified
“…A emissão de poluentes atmosféricos em grandes centros está relacionada à frota veicular que circula pelas vias, e a idade dos veículos é um fator determinante para a qualidade do ar (KUHNS et al, 2004;KRECL et al, 2015). Isso porque conduções com maior desgaste de peças e com tecnologias ultrapassadas podem contribuir com até 34% da emissão total de CO, NO e hidrocarbonetos em uma cidade (GUO et al, 2006).…”
Section: Introductionunclassified